Human gingival derived neuronal cells in the optimized caffeic acid hydrogel for hemitransection spinal cord injury model. Issue 3 (23rd October 2019) - Subbarayan, Rajasekaran; Barathidasan, Rajamani; Raja, Selvaraj T. K.; Arumugam, Gnanamani; Kuruvilla, Sarah; Shanthi, Palanivelu; Ranga Rao, Suresh
Abstract: Spinal cord injury induces scar formation causes axonal damage that leads to the degeneration of axonal function. Still, there is no robust conceptual design to regenerate the damaged axon after spinal injury. Therefore, the present study demonstrates that human gingival derived neuronal stem cells (GNSCs) transplants in the injectable caffeic acid bioconjugated hydrogel (CBGH) helps to bridge the cavity and promote the engraftment and repopulation of transplants in the injured spinal tissue. Our study reports that the bioluminescence imaging in vivo imaging system (IVIS) provides a satisfactory progression in CBGH‐GNSCs transplants compare to lesion control and CBGH alone. Immune regulators interleukin‐6 (IL‐6), tumor necrosis factor‐α, neutrophil elastase are decreased, IL‐10 is increased. Likewise, immunostaining (TAU/TUJ‐1, SOX‐2/NeuN, MAP‐2/PSD93, NSE, S100b, and GFAP) shown repopulated cells. Also, TRA‐1‐81 expression confirms the absence of immune rejection in the CBGH‐GNSCs transplants. However, locomotor recovery test, gene (IL‐6, CASPASE3, p14‐ARF, VEGF, LCAM, BDNF, NT3, NGN2, TrKc, FGF2, Sox‐2, TUJ‐1, MAP‐2, Nestin, and NeuN) and protein expression (TAU, TUJ‐1, SOX‐2 MAP‐2, PSD93, NeuN, TRA‐1‐81, GFAP, TAU, and MBP) shows functional improvements in the CBGH‐GNSCs group. Further, GABA and glutamine level demonstrates the new synaptic vesicle formation. Hence, the CBGH scaffold enhances GNSCs transplants to restore the injured spinal tissue. Abstract : Schematic representation shows the chemistry of caffeic acid bioconjugated hydrogel, gingiva‐derived mesenchymal stem cells culture, neuronal induction, encapsulation, and transplantation into the hemitransection spinal cord rat injury model.